The healing power of essential oils : soothe inflammation, boost mood, prevent autoimmunity, and feel great in every way - Zielinski, Eric (Harmony Books, 2018)
"Eric Zielinski, D.C., host of the Essential Oils Revolution summits, offers a soup-to-nuts guide to mastering essential oils for vibrant health and well-being, featuring dozens of recipes and formulations for restful sleep, reduced inflammation, balanced hormones, and more. Achieving true health is not an easy task. For many people, it might be easier to pop a pill or push aside lingering discomfort in favor of finishing everything on your to-do list. In The Healing Power of Essential Oils, Eric Zielinski, D.C. shows readers how to make their health a priority with the life-changing benefits of essential oils. Essential oils are the natural solution to everything from anxiety and depression to deep-seated inflammation. For beginners, Dr. Z teaches everything you need to know to get started, including the top seven oils you should stock from Day 1 and the commonly used techniques and tools. He illustrates daily practices you can follow to enjoy the properties of essential oils, including a five-minute devotional using frankincense and neroli to set you up for a productive and stress-free day, and a simple bedtime routine harnessing the soporific effects of lavender. Backed by extensive research, Dr. Z also supplies essential oil blends that promote hormone balance, reduced inflammation, improved digestion, increased immunity, and so much more. You'll be armed with over 150 recipes for every health need, and a special section on women's health includes dozens of formulations for PMS, fertility, pregnancy, candida, and menopause. Even those well-versed in essential oils will benefit from this thorough approach. With your newfound knowledge, you can begin tailoring an essential oils practice to your unique pain points and lifestyle right away - and start experiencing amazing results"--